Performance of Broiler Chicks (Gallus domesticus) Fed Maize Offal-Based Diets Supplemented with Roxazyme G Enzyme - Nnenna, Onu Patience; Emeka, Nwakpu Petrus; Okpoko, Chukwu Leonard (International Journal of Poultry Science, 2006)
An experiment was conducted to evaluate the performance of broiler chicks fed maize offal-based diets supplemented with roxazyme G enzyme. Seven experimental diets were formulated such that diet T1 which served as the control, contained 0% maize offals and without enzyme supplementation. Diets T2 and T5 served as control for enzymes at increased levels of maize-offal supplementation. Diets T3 and T4 contained 20% maize offal supplemented with 100 mg and 200 mg of enzyme respectively, while diets T6 and T7 contained 40 % of maize offal supplemented with 100 mg and 200 mg of enzyme respectively. One hundred and forty seven (147) 4 week-old Anak broiler chicks were randomly assigned to the seven diets in a completely randomized design (CRD). Each treatment was replicated thrice with seven (7) birds per replicate. The experiment lasted for 28 day. Results showed that there were significant differences in the performance of the birds on the treatment groups in all the measurements recorded. Birds fed the control 1 diet had the highest weight gain and best feed conversion ratio, though this was not significantly higher than those fed diet T3. There was no significant (P > 0.05) difference between the weight gain of the birds fed diets T3, T4 and T7. There was a significant (P < 0.05) decrease in weight gain as dietary level of maize offal increased without enzyme supplementation. The feed intake of bird fed diet T5 was significantly (P < 0.05) higher than those fed other treatment diets. The feed conversion ratio of birds fed T1, T3 and T4 diets did not differ significantly (P > 0.05). Though there were significant (P < 0.05) differences on the feed conversion ratio of birds fed diets T2, T5 and T6 , there was no significant (P > 0.05) difference on the feed conversion ratio of birds fed diets T3, T4 and T7. The result of the experiment showed that with Roxazyme G supplementation at either 100 mg or 200 mg/kg feed, maize offal can replace maize in the diets at up to 20 % level without any deleterious effect. However, at 40 % inclusion level, 200 mg/kg feed proved more effective. Economics of production showed that Roxazyme G supplementation were profitable as regards the cost of feed per kg weight gain and thus cost savings.